2012
DOI: 10.5152/jtgga.2012.07
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the contraceptive method choice: a University hospital experience

Abstract: Objective:To analyze the factors influencing behavior of women in choosing contraceptive methods. Material and Methods:A total of 4022 women who were admitted to our clinic in a year, were the subjects in this current study for contraception choices. Relationship between the current contraceptive choice and the age, marital status, educational level, gravidity and induced abortions were evaluated.Results: Current users of any contraceptive methods were found to make up thirty-three percent of the entire study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 8 publications
0
13
0
5
Order By: Relevance
“…This finding is inconsistent with studies done in Turkey and Kenya. This could be lack of awareness on permanent contraceptive methods (tubal ligation and Vasectomy) in this study area [ 11 , 12 ]. In multivariable analysis educational attainment was important predictors of long acting and permanent contraceptive methods.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is inconsistent with studies done in Turkey and Kenya. This could be lack of awareness on permanent contraceptive methods (tubal ligation and Vasectomy) in this study area [ 11 , 12 ]. In multivariable analysis educational attainment was important predictors of long acting and permanent contraceptive methods.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that easy to use, low expense and no need to medical care and advice are the most important factors behind selection of withdrawal as method of contraception (9). Given that last review on the role of education in selection of right Bangladesh, respectively (11)(12)(13). Women with higher number of children hopefully tend to have long lasting and more powerful method of contraception.…”
Section: Discussionmentioning
confidence: 99%
“…Pek çok çalışma bu sonuca ulaşmış ve geleneksel sosyal yapı, bilgi kaynağının arkadaşlar oluşu, düşük eğitim düzeyi, hizmet sunan servislerin yeterli olmayışı ve Türk toplumunda erkeğin daha fazla cinsel deneyimi oluşuyla sonuç açıklanmıştır (4)(5)(6)(7)(8) .…”
Section: Kontrasepsiyon Kullanma Süresi (Ay)unclassified
“…Bu ilişki Türkiye'den ve diğer bazı ülkelerden yapılan çalışmalarda da gözlem-lenmiştir (4,7,14,15) . İkinci evliliğini yapmış kadınlarında tercih ettiği yöntemdir.…”
Section: Kontrasepsiyon Kullanma Süresi (Ay)unclassified
See 1 more Smart Citation